Spatio-temporal variations of ecosystem service values in response to land use/cover change in Luoyang city - Yin, Junru; Liu, Xuan; Wang, Hua; Huang, Wei; Cai, Enxiang (Frontiers in Environmental Science, 2022)
Land-use/cover change (LUCC) caused by human activities is an important factor in changes in global ecosystems; however, the impact of LUCC on ecosystem service value (ESV) has never been previously assessed in Luoyang City, China. This paper explores spatial and temporal evolution patterns of land use pattern change, ESV change and response to LUCC in Luoyang City from 2010 to 2019 through GIS and remote sensing techniques, and employing transfer matrix, ESV spatial autocorrelation analysis and elastic coefficient change. During the study period: 1) Between 2010 and 2019, land-use changes in Luoyang City showed a trend of “two increases and four decreases,” specifically, built-up land and forest areas increased, while the extent of cropland, grassland, water, and unused land areas decreased. 2) The recorded land-use conversion in Luoyang City is complex, with forest and cropland land uses increasing and decreasing fastest, respectively, with the proportion of forest increasing by 10.19% and cropland decreasing by 3.37% — the reason for this change is the transition from cropland and grassland to forest and occupation of cropland by built-up land. 3) The ESV change in Luoyang City was U-shaped, with the total ESV increasing 1.96% from ¥44.78 billion to ¥45.66 billion; additionally, the ESV provided by forest areas increased by 23.83%. 4) From 2010 to 2019, Luoyang’s hydrological regulation, climate regulation and soil and water conservation contributed the most to Luoyang’s ESV, accounting for 63.89% of the total ESV in 2019. 5) The overall ESVs of the townships in Luoyang City have obvious clustering and are not completely randomly spatially distributed. With the optimization of land-use allocation, the ESV high–high clusters have expanded. 6) The overall elasticity coefficient is high in Luoyang City and ESV responds intensely to LUCC, with the most significant response shown by the forests of Luolong District. The findings of this survey are practical for helping Luoyang City to optimize land resource usage scientifically.